SLC41A2 Suppresses Colon Cancer Progression by Inhibiting GSK3β Ubiquitin-proteasome Degradation - Lu, Yueyao; Shen, Ying; Liu, Jinsong; Deng, Jianzhong; Wang, Yue; Liu, Qian; Lu, Wenbin (Current Molecular Medicine, 2025)
<span class=
Keywords: Colon cancer